Réponses

2013-07-12T20:37:04+02:00

1)  A  =  7/15 - 2/15 × 9/4

          =  7/15 - 1/15 × 9/2

          =  14/30 - 9/30

          =  5/30

          =  1/6

 

 

2)  B  =  (25 × 10⁶ × 3 × 10⁻²) : (2 × 10²)

          =  (75 × 10⁴) : (2 × 10²)

          =  75/2 × 10⁴⁻²

          =  37,5 × 10²

          =  3,75 × 10³

          =  3750

 

 

3)   a.   C  =  3√72 - 5√2

                  ≈  18,385

 

       b.   C  =  3√72 - 5√2

                  =  3√(36 × 2) - 5√2

                  =  3 × 6√2 - 5√2

                  =  (18 - 5)√2

                  =  13√2